1992
DOI: 10.1128/aem.58.8.2543-2551.1992
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bioaerosol sampling methods in barns housing swine

Abstract: The air in livestock buildings contains bioaerosol levels that are sufficiently high to cause adverse health effects in animals and workers. These bioaerosols are complex mixtures of live and dead microorganisms and their products as well as other aeroallergens. The effectiveness of sampling methods used for quantifying the very high concentrations of microorganisms in these environments has not been well studied. To facilitate an accurate assessment of respiratory hazards from viable organisms in agricultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(53 citation statements)
references
References 45 publications
0
48
0
Order By: Relevance
“…Interpretation of results from field studies is complicated by the delay caused by transport of samples to a laboratory before the samples are plated. Such delay gives the organisms an opportunity to multiply or die in transit (Thorne, Kiekhaefer, Whitten, & Donham, 1992). Although the effect of storage time and temperature on survival of bacterial and fungal aerosols collected using impingers has been reported (Li & Lin, 2001;Lin & Li, 2003), the effect on survival of virus aerosols has not yet been reported until our current study.…”
Section: Introductionmentioning
confidence: 68%
“…Interpretation of results from field studies is complicated by the delay caused by transport of samples to a laboratory before the samples are plated. Such delay gives the organisms an opportunity to multiply or die in transit (Thorne, Kiekhaefer, Whitten, & Donham, 1992). Although the effect of storage time and temperature on survival of bacterial and fungal aerosols collected using impingers has been reported (Li & Lin, 2001;Lin & Li, 2003), the effect on survival of virus aerosols has not yet been reported until our current study.…”
Section: Introductionmentioning
confidence: 68%
“…For detecting airborne bioaerosols, one should rely on many forms of cultivation media such as malt extract agar (MEA) (Lehtinen et al, 2013), Sabouraud dextrose agar (SDA) , dichloran rose-bengal chloramphenicol (DRBC) (Tolvanen and Hänninen, 2006), and yeast extract glucose chloramphenicol (YGC) (Borrego et al, 2012). In one of the previous studies, Thorne et al (1992) concluded that the all-glass impinger method was the best method for collecting total bacteria and fungi while the microbial sampler method was used preferably for sampling enteric organisms. In another study, it was also found that impingers for sampling airborne bacterial bioaerosols could be used with a better performance than filtration methods (Li, 1999).…”
Section: Sampling Of Bioaerosolsmentioning
confidence: 99%
“…The results of previous studies confirm the considerable effects of seasonal factors on the observed levels of bioaerosols. In a wastewater treatment unit in Tehran, Iran, the average concentrations of bacterial bioaerosols in winter and summer were measured as 1016 and 1973 colony-forming unit (CFU)FND/ m 3 , respectively (Thorne et al, 1992). The concentrations of fungi and bacteria measured from the bedroom of six contemporary, airtight dwellings in the USA during winter ranged from 3 to 59 (mean 18.4) and 19-607 (mean 212) CFU/m 3 , respectively (McGill et al, 2015).…”
Section: Fungi and Bacteriamentioning
confidence: 99%
“…The recommended maximum duration of the sampling period for the AGI-30 is 30 min. Impactors may easily become overloaded when samples are taken in livestock houses (Thorne et al, 1992), therefore, the sampling duration is limited to minutes or even to seconds. Filtration method would not encounter the problems (evaporation of sampling liquid and overloading) of impingers and impactors; however, long sampling duration by filtration may not benefit in microorganism collection because of the biological decay of microorganisms owing to dehydration (Griffin et al, 2011;Wang et al, 2001).…”
Section: Sampling Strategymentioning
confidence: 99%
“…In some studies, the efficiency has been evaluated by comparing samplers side by side in an environment with unknown microbial concentration (Engelhart et al, 2007;Henningson et al, 1982;Thorne et al, 1992). This method easily ranks the performance of different samplers; however, it neither reveals whether the amount of microorganisms collected in the samples accurately represents the microorganism content of the air nor distinguishes between the physical and biological efficiency.…”
Section: Samplers For Microorganismsmentioning
confidence: 99%